A single point mutation in the TRPC3 lipid-recognition window generates supersensitivity to benzimidazole channel activators. (May 2019) - Svobodova, Barbora; Lichtenegger, Michaela; Platzer, Dieter; Di Giuro, Cristiana M.L.; de la Cruz, Gema Guedes; Glasnov, Toma; Schreibmayer, Wolfgang; Groschner, Klaus
Graphical abstract: Highlights: A glycine residue (G652) within the pore domain of TRPC3 determines the channel´s sensitivity to benzimidazole agonists. Mutation of G652 to alanine generates supersensitivity to benzimidazoles, while occluding physiological activation of TRPC3. Single channel analysis reveals a long-lived open state as the basis of supersensitivity to benzimidazoles. Inactivation/desensitization of TRC3 by physiological stimuli and diacylglycerols is largely eliminated by the G652A mutation. Abstract: Mutation of a single residue within the recently identified lipid (diacylglycerol) recognition window of TRPC3 (G652A) was found to abolish channel activation via endogenous lipid mediators while retaining sensitivity to the non-lipid activator GSK1702934A (abb. GSK). The mechanism of this change in chemical sensing by TRPC3 was analysed by whole-cell and single channel electrophysiology as well as Ca 2+ imaging. Currents initiated by GSK or the structural (benzimidazole) analog BI-2 were significantly larger in cells expressing the G652A mutant as compared to wild type (WT) channels. Whole cell patch-clamp experiments revealed that enhanced sensitivity to benzimidazoles was not due to augmented potency but reflected enhanced efficacy of benzimidazoles. Single channel analysis demonstrated that neither unitary conductance nor I-V characteristics were altered by the G652A mutation, precluding altered pore architecture as the basis of enhanced efficacy. These experiments uncovered a distinct gating pattern of BI-2-activated G652A mutant channels, featuring a unique, long-lived open state. Moreover, G652A mutant channels lacked PLC/diacylglycerol mediated cross-desensitization for GSK activation as typically observed for TRPC3. Lack of desensitization in G652A channels enabled large GSK/BI-2-induced Ca 2+ signals in conditions that fully desensitized TRPC3 WT channels. We demonstrate that the lipid-recognition window of TRPC3 determines both sensitivity to lipid mediators and chemical gating by benzimidazoles. TRPC3 mutations within this lipid interaction site are suggested as a basis for chemogenetic targeting of TRPC3-signaling.